Konsumgut Nachhaltigkeit: Zur Inszenierung neuer Leitmotive in der Produktkommunikation - Gekeler, Moritz (transcript, 2014)
Products are the media of consumer culture – they tell us stories. For a few years now, »sustainability« has been a dominant topic in these stories. This book looks into the staging strategies of companies, who with the help of product design, advertising and marketing, tell stories about sustainability. It investigates the various protagonists from the perspective of narratology and media theory, and describes their respective roles in communicative processes. Beyond this, the opportunities and risks of these burgeoning sustainability communications are also illustrated, as well as the increasing pressure for radical innovation.